A prática pedagógica dos docentes da área da música da Licenciatura em Educação do Campo – Campus Arraias/UFT - Silva, Jane Monteiro da (Universidade Federal do Tocantins, 2023)
The present study sought to know the didactic-pedagogical practice of teachers in the music area of the Degree of Rural Education at the Arraias University, UFT campus. For this, we developed a study with a qualitative approach, whose technical procedures gave rise to a case study. We try to understand, from the observation and the speeches, how these teachers put into practice the pedagogical processes for the teaching of different disciplines in the area of music. We wanted to understand what knowledge they had, what their strategies were, what were the philosophies that guided these practices. Thus, the study was developed in four stages: a) in the first stage, the project was presented to the five professors of the Music area of the Bachelor's degree, for their knowledge and authorization to develop the study regarding the observation of their classes and the definition of which subjects were more favorable to follow; b) the second stage involved the activity of surveying and deepening the literature on the subject, the beginning of observation in the classroom and the preparation of guides for interviews and observations; c) the third stage, interviews were conducted with teachers and their transcripts; d) the fourth stage gave rise to the analysis and interpretation of data and the writing of the final report. From the analysis of the collaborators' speeches, we conclude and verify that there is a consensus among teachers about the need for articulation between the technical, human and political dimensions. Classroom observations highlighted the need to integrate theory-practice and to reflect on and analyze different theories in order to confront practice. We also evidence a point of convergence between the discourses and practices of teachers: social commitment, a contextualized vision, the link to a historical process of their training paths and concern for the sociocultural reality of students. It is hoped that the results of this study will inspire future research and contribute to researchers who intend to work on the same topic.